THE SIGNING OF THE NOTARY DEED IS NOT THE SAME TIME: FINDING OF LAW OR VIOLATION OF LAW - Udin Narsudin (Jurnal Scientia, 2023)
The Covid-19 pandemic has created various problems in various ways, including the notary world. In its development as a result of the enactment of the Enforcement of Restrictions on Community Activities (PPKM) an opinion emerged which stated that the signing of the deed before a notary could not be at the same time. Based on the provisions of Article 16 paragraph (1) letter m UUJN and Article 44 paragraph (1) UUJN which are coercive provisions it is not possible to deviate or exclude, therefore violation of them is a form of unlawful act.